The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1093/burnst/tkac061
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in the brain after peripheral burns

Abstract: Brain injuries are common complications in patients with thermal burns and are associated with unpleasant outcomes. In clinical settings, it was once believed that brain injuries were not major pathological processes after burn, at least in part due to the unavailability of specific clinical manifestations. Burn-related brain injuries have been studied for more than a century, but the underlying pathophysiology has not been completely clarified. This article reviews the pathological changes in the brain follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 139 publications
1
6
0
Order By: Relevance
“…It was manifested through the increase in the relative expression of the pro-apoptotic (Bax) and a decline in the anti-apoptotic (Bcl-2) markers. This finding is in line with the previously described brain injury following peripheral burn injury that was manifested in neurons and microglia [ 5 ]. Again, all protocols applied to minimize the thermal wound and improve healing simultaneously and successfully reversed the pro-apoptotic alterations in the hippocampal tissue in this study ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It was manifested through the increase in the relative expression of the pro-apoptotic (Bax) and a decline in the anti-apoptotic (Bcl-2) markers. This finding is in line with the previously described brain injury following peripheral burn injury that was manifested in neurons and microglia [ 5 ]. Again, all protocols applied to minimize the thermal wound and improve healing simultaneously and successfully reversed the pro-apoptotic alterations in the hippocampal tissue in this study ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Figure 8 , it seems that the initial pro-inflammatory and pro-apoptotic impact of a thermal injury may contribute to the lowering of hippocampal BDNF by affecting neurons after peripheral burns [ 5 ]. This may be attributed to the cut down of GABA-AR expression [ 45 ], and consequent anxiogenic response, as previously described by Stajic and coworkers [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, glucocorticoids have been demonstrated to inhibit the transition of cells from the G0/G1 to S phase, suggesting their potential use for HS treatment. 34 However, due to the fast plasma clearance, the treatment effects of MPSS only last for a short time. [35][36][37] Previous studies demonstrated that drug-loaded ZIF-90 nanocomposites can protect the drugs from rapid degradation during circulation and undergo controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Shock in the burn patient is due to the combination of hypovolemic shock and cellular shock, characterized by specific microvascular and hemodynamic alterations [1]. After injury, there is a significant loss of circulating plasma volume due to increased capillary permeability, which is derived from vascular injury and the release of inflammatory mediators [2]. As a result, edema emerges in both burned and unburned tissues, followed by the depletion of intravascular volume, reduced cardiac output and increments in systemic vascular resistance [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%